Left Ventricular Longitudinal Contractility Predicts Acute‐on‐Chronic Liver Failure Development and Mortality After Transjugular Intrahepatic Portosystemic Shunt. Issue 3 (22nd January 2019) - Jansen, Christian; Schröder, Anna; Schueler, Robert; Lehmann, Jennifer; Praktiknjo, Michael; Uschner, Frank E.; Schierwagen, Robert; Thomas, Daniel; Monteiro, Sofia; Nickenig, Georg; Strassburg, Christian P.; Meyer, Carsten; et al.
Abstract : Acute deterioration of liver cirrhosis (e.g., infections, acute‐on‐chronic liver failure [ACLF]) requires an increase in cardiac contractility. The insufficiency to respond to these situations could be deleterious. Left ventricular global longitudinal strain (LV‐GLS) has been shown to reflect left cardiac contractility in cirrhosis better than other parameters and might bear prognostic value. Therefore, this retrospective study investigated the role of LV‐GLS in the outcome after transjugular intrahepatic portosystemic shunt (TIPS) and the development of ACLF. We included 114 patients (48 female patients) from the Noninvasive Evaluation Program for TIPS and Their Follow‐Up Network (NEPTUN) cohort. This number provided sufficient quality and structured follow‐up with the possibility of calculating major scores (Child, Model for End‐Stage Liver Disease [MELD], Chronic Liver Failure Consortium acute decompensation [CLIF‐C AD] scores) and recording of the events (development of decompensation episode and ACLF). We analyzed the association of LV‐GLS with overall mortality and development of ACLF in patients with TIPS. LV‐GLS was independently associated with overall mortality (hazard ratio [HR], 1.123; 95% confidence interval [CI], 1.010‐1.250) together with aspartate aminotransferase (HR, 1.009; 95% CI, 1.004‐1.014) and CLIF‐C AD score (HR, 1.080; 95% CI, 1.018‐1.137). Area under the receiver operating characteristic curve (AUROC) analysis for LV‐GLS for overall survival showed higher area under the curve (AUC) than MELD and CLIF‐C AD scores (AUC, 0.688 versus 0.646 and 0.573, respectively). The best AUROC‐determined LV‐GLS cutoff was −16.6% to identify patients with a significantly worse outcome after TIPS at 3 months, 6 months, and overall. LV‐GLS was independently associated with development of ACLF (HR, 1.613; 95% CI, 1.025‐2.540) together with a MELD score above 15 (HR, 2.222; 95% CI, 1.400‐3.528). Conclusion: LV‐GLS is useful for identifying patients at risk of developing ACLF and a worse outcome after TIPS. Although validation is required, this tool might help to stratify risk in patients receiving TIPS. Abstract : Increase in cardiac contractility is required in physical stress situations due to acute deterioration of liver disease (e.g. acute‐on‐chronic liver failure (ACLF)) or interventions (e.g. transjugular intrahepatic portosystemic shunt (TIPS)). The insufficiency to respond to these situations might be deleterious. This study demonstrated the usefulness of LV‐GLS to identify patients at risk of developing ACLF and worse outcome after TIPS.